2017
DOI: 10.1016/j.bodyim.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The importance of body image concerns in overweight and normal weight individuals with binge eating disorder

Abstract: Body image concerns in binge eating disorder (BED) have been examined almost exclusively in overweight individuals with BED. The current study extends past research by including overweight and normal weight BED and non-BED groups to assess the multifactorial construct of body image using subscales of the Eating Disorder Examination 16.0 (EDE-16.0) and a Body Comparison Task. Independent of weight status and when controlling for age and race, women with BED are distinguished from those without BED by significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 79 publications
3
8
0
1
Order By: Relevance
“…The results of this study showed that the participants who were dissatisfied with their weight scored the highest eating attitude scale median, whereas the same result was not obtained in the participants who were dissatisfied with their body image. This finding is consistent with the results of the studies [25,27]. Similarly, our results are compatible with the results of the studies [23,26] published previously.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of this study showed that the participants who were dissatisfied with their weight scored the highest eating attitude scale median, whereas the same result was not obtained in the participants who were dissatisfied with their body image. This finding is consistent with the results of the studies [25,27]. Similarly, our results are compatible with the results of the studies [23,26] published previously.…”
Section: Discussionsupporting
confidence: 94%
“…The parallel results of another study carried out [26] showed that adolescents' self-perception of being overweighed was associated with unhealthy weight control behaviors during the young adulthood period. Another supporting study on this issue [27] suggested that significantly greater overvaluation of shape, weight and significantly reduced weight satisfaction distinguished women with binge eating disorder (BED) from those without BED. On the contrary, another study has suggested that body dissatisfaction increases the risk of bulimic pathology in the following years [28].…”
Section: Perceived Weight and Body Imagementioning
confidence: 99%
“…Consistent with prior investigations of primarily White/Caucasian men and women (Ahrberg, Trojca, Nasrawi, & Vocks, ; Yiu, Murray, Arlt, Eneva, & Chen, ), body image concerns, including concerns with body fat and muscularity, were positively associated with LOC eating frequency in young Hispanic/Latino men living in the United States, even after adjusting for body size. Both theoretical and empirical data suggest that this relationship may be due to negative affect and/or rigid dietary restraint associated with body image concerns, which are common precipitants to LOC eating (Berg et al, ; Dakanalis, Clerici, et al, ; Dakanalis, Pla‐Sanjuanelo, et al, ; Haedt‐Matt & Keel, ; Stice, Shaw, & Nemeroff, ).…”
Section: Discussionsupporting
confidence: 84%
“…Health-related advertisements sometimes perpetuate the so-called 'healthy weight' stereotype that being beautiful and healthy is only achieved by reducing body fat (Rodgers, 2016). However, greater concerns about weight do not necessarily lead to healthy habits or health consciousness (McCabe, Connaughton, Tatangelo, Mellor & Busija, 2017;Yiu, Murray, Arlt, Eneva & Chen, 2017). Therefore, healthy behaviors should be stimulated to facilitate positive self-image of university students.…”
Section: Discussionmentioning
confidence: 99%